Capillary endothelial cells as coordinators of skeletal muscle blood flow during active hyperemia. (April 2017) - Murrant, Coral L.; Lamb, Iain R.; Novielli, Nicole M.
Abstract: In this invited review, we explore the burgeoning possibility of capillary endothelial cells as coordinators of skeletal muscle blood flow in response to muscle contraction. The idea that the capillary is an active vascular unit in skeletal muscle microcirculation starkly diverges from the traditional dogma that seats arterioles as the central controllers of blood flow during exercise. This review aims to incite discussion as we revisit and rethink the role of capillary endothelial cells in skeletal muscle. We discuss the potential for a mismatch in the architectural relationships between the arteriolar microvasculature and contracting motor units that would negate consistent communication between them. We review the data from the past two decades demonstrating that capillaries are ideally located architecturally to communicate with skeletal muscle fibers and are mechanistically capable of signaling upstream arterioles that control their own perfusion. We show that the orchestration of a coordinated vascular response necessary to support active skeletal muscle fibers cannot be achieved by the arterioles, but rather it is the capillaries that drive the blood flow response to muscle contraction. Thus, capillaries need to be seriously considered as critical in the coordination of skeletal muscle blood flow during active hyperemia.